"Association splitting" versus cognitive remediation in obsessive-compulsive disorder: A randomized controlled trial. (May 2018) - Jelinek, Lena; Hauschildt, Marit; Hottenrott, Birgit; Kellner, Michael; Moritz, Steffen
Highlights: Association splitting (AS) is highly accepted when used in face-to-face therapy. There is no additional effect of AS beyond CBT treatment in OCD. AS is superior when control patients with knowledge of AS were excluded. Information exchange between patients should be controlled for in trials. Abstract: Studies have confirmed the efficacy of the cognitive intervention Association Splitting (AS) in obsessive-compulsive disorder (OCD) when applied as a self-help technique. AS aims to alter symptom-provoking automated cognitive networks of OC-related stimuli by building new or strengthening established but weak neutral associations. The aim of this study was to investigate the acceptance and benefits of therapist-assisted AS as an add-on to cognitive behavioral therapy (CBT). One hundred and nine patients with OCD who were undergoing CBT were randomly assigned to either AS or cognitive remediation (CR). Both groups were assessed at baseline, 4 weeks and 6 months later. The primary measure was the Yale-Brown Obsessive Compulsive Scale. Although patients' acceptance of AS was good, AS was not better than CR regarding overall symptom severity. However, a larger decrease was found from baseline to 6 months follow-up in AS regarding avoidance. Moreover, subsidiary analyses excluding control patients who had obtained information about AS indicated its superiority. Because superiority of AS was found in post hoc analyses excluding control patients who had obtained information on AS, we suggest that contagion effects deserve consideration.